Qualitative Analysis of Solutions of Nonlinear Delay Dynamic Equations. (30th December 2013) - Ünal, Mehmet; Raffoul, Youssef N.
Abstract : We use the fixed point theory to investigate the qualitative analysis of a nonlinear delay dynamic equation on an arbitrary time scales. We illustrate our results by applying them to various kind of time scales.